Drought stress‐induced changes in starch yield and physiological traits in potato. (17th July 2017) - Rudack, K.; Seddig, S.; Sprenger, H.; Köhl, K.; Uptmoor, R.; Ordon, F.
Abstract: Drought stress is an important limitation for potato ( Solanum tuberosum L.) production as potato depends on appropriate water availability for high yields of good quality. Therefore, especially in the background of climate change, it is an important goal in potato breeding to improve drought stress tolerance. In this study, 34 European starch potato cultivars were evaluated for drought stress tolerance by growing under well‐watered and long‐term drought stress conditions in rainout shelters in 2 years' pot trials. Besides yield, six physiological traits, that is free proline content, osmolality, total soluble sugar content, chlorophyll content (SPAD), cell membrane stability and crude protein content, were determined in leaves sampled during vegetative growth and during flowering to investigate their association with drought tolerance. ANOVA revealed significant treatment effects for all physiological traits and increased genotypic effects at flowering. The sensitivity of physiological traits to drought was significantly higher during flowering than during vegetative growth. Drought stress decreased starch yield significantly ( p < .001), on average by 55%. Starch yield was significantly influenced by genotype and genotype × treatment interactions. Stress tolerance index (STI) calculated from starch yield ranged from 0.26 (sensitive) to 0.76 (tolerant) with significant genotype effects ( p ≤ .001). STI correlated positively with cell membrane stability ( r = .59) and crude protein content ( r = .38) and negatively with osmolality ( r = −.57) and total soluble sugar content ( r = −.71). These contrary correlations suggest a dual adaptation strategy in potato under long‐term drought stress conditions including increased membrane stability combined with an increased osmolality due to an increased soluble sugar content.